Selective Policy Regarding the Granting of Foreign Stay Permits Based on Indonesian State Sovereignty - Wiharma, Cecep; Mulyadi , Muhamad Budi; Jusuf Wirahma, Baharuddin (Yayasan Studi Cendekia Indonesia (YSCI), 2024)
Many cases of misuse of residence permits are handled by immigration authorities by taking firm action in the form of administrative or criminal acts against foreign nationals. The purpose of this study is to explore the relationship between selective policies and legal frameworks, examining how selective policies are aligned with existing laws and regulations. The data obtained is analysed qualitatively with a normative juridical approach, by utilizing secondary data obtained through document studies, which includes the systematic organization of written legal materials. The results of the study show that the form of selective policy has an impact on granting residence permits to foreign nationals based on the sovereignty of the State of Indonesia. The most significant difference is that visa applications for foreigners from countries calling for visas require certain stages, namely recommendations from the assessment coordination team of the country calling for visas to consider the feasibility of the visa application submitted. The purpose and intention of entering Indonesian territory will also be assessed, along with the suitability of the visa application. The study also investigated.